Observational comparative study in pregnant females between normal thyroid profile and subclinical hypothyroidism in first trimester and its effect on pregnancy and fetomaternal outcome - Shalini,; Patel, Sugandha (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2025)
Background: Subclinical hypothyroidism (SH) by definition means there is increased in serum thyroid stimulating hormone (TSH) and normal free T4 and free T3. Normal range of serum TSH according to trimester is given below (as per American Thyroid Association and Endocrine Society Clinical Practice Guidelines recommendations): 1st trimester: 0.1 to 2.5 mIU/l; 2nd trimester: 0.2 to 3.0 mIU/l; 3rd trimester: 0.3 to 3.0 mIU/l. Numerous studies have demonstrated association of SH with adverse pregnancy related outcome while some studies found no association. This study was conducted to study about SH in pregnancy and its impact on fetomaternal outcomes. Methods: This was a hospital based prospective case control study, conducted on 100 women taking routine antenatal care between year 2023 and 2024. The participants were divided into two groups - case: antenatal women in 1st trimester with SH, and control: antenatal women with 1st trimester with normal thyroid profile. These women were followed till their delivery and their maternal and neonatal outcomes were compared. Results: Women with SH reported increased risk of complications (anaemia, preeclampsia, postdatism, oligohydramnios, more NICU admissions and low APGAR score). Conclusions: Evaluation for altered thyroid profile in early pregnancy should be done routinely and timely intervention for treatment even for subclinical hypothyroidism to be done. It will lead to decrease in all complications and will improve the maternal and neonatal outcome.